1984
DOI: 10.1007/bf00175380
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I trial of Cis-diammine-1,1-cyclobutane dicarboxylate platinum II (Carboplatin, CBDCA, JM-8) with a single dose every five week-schedule

Abstract: Carboplatin, a new platinum analogue, was administered intravenously on a schedule of a single dose every five weeks to 23 patients with advanced malignant solid tumors. Patients were treated at six dosage levels ranging from 200-550 mg/m2 every five weeks. Thrombocytopenia was dose-limiting. At 550 mg/m2 Carboplatin, the median platelet nadir was 65 000/mm3. Leukopenia was common, but usually of mild to moderate degree. Gastrointestinal upset was commonly seen at all dose levels, but 35% of the patients exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In preclinical studies, CDBCA was associated with markedly improved nephrotoxicity and reduced gastrointestinal toxicity, but more severe hematotoxicity, compared with CDDP. Phase I studies of CBDCA were primarily conducted in Europe and America [5][6][7], and showed that the dose-limiting factor (DLF) was hematotoxicity, as expected. In a Japanese phase I study, the DLFs were thrombocytopenia and leukopenia, and nephrotoxicity was mild and reversible, with a primary clinical toxicity of gastrointestinal disorder [8,9].…”
Section: Discussionmentioning
confidence: 92%
“…In preclinical studies, CDBCA was associated with markedly improved nephrotoxicity and reduced gastrointestinal toxicity, but more severe hematotoxicity, compared with CDDP. Phase I studies of CBDCA were primarily conducted in Europe and America [5][6][7], and showed that the dose-limiting factor (DLF) was hematotoxicity, as expected. In a Japanese phase I study, the DLFs were thrombocytopenia and leukopenia, and nephrotoxicity was mild and reversible, with a primary clinical toxicity of gastrointestinal disorder [8,9].…”
Section: Discussionmentioning
confidence: 92%
“…The clinical introduction and use of platinum–based chemotherapeutics, specifically cis -diamminedichloroplatinum(II) (cisplatin), significantly improved overall survival (OS) by ~6 months in 29% of patients with ovarian cancer, leading the way to its adoption as the backbone of most chemotherapeutic regimens [1, 2]. In the mid-1980’s, a cisplatin analog, Carboplatin [cis-diammine(1,1-cyclobutanedicarboxylato)platinum(II)], with an improved toxicity profile and equivalent therapeutic efficacy, replaced cisplatin as standard of care [35]. The last major advance occurred in the early 1990's with the introduction of the mitotic inhibitor, paclitaxel, that further improved OS 3-15 months (depending on the study) when used in combination with platinum [68].…”
Section: Introductionmentioning
confidence: 99%
“…These facts may explain the higher reactivity of JM-40 compared to carboplatin, and also why, from a pharmacokinetic point of view, JM-40 seems to be more related to cis-platin than to carboplatin (Vermorken et al, 1984bElferink et al, submitted;Harland et al, 1984). Besides, the dose-limiting toxicities of JM-40 (nephro and gastro-intestinal toxicity, (Winograd et al, 1986)) are similar to that of cis-platin, whereas the dose limiting toxicity of carboplatin is myelotoxicity (Joss et al, 1984). Vermorken et al (1985) indicated a relationship between the nephrotoxic properties of 6 platinum complexes and their stability in aqueous solution.…”
Section: Discussionmentioning
confidence: 99%